Trachyonychia in a child with concomitant alopecia areata and lichen planus - David, Abhinav; Kaur, Inderpreet (International Journal of Research in Dermatology, 2021)
Trachyonychia of nails has been found to be associated with dermatoses such as lichen planus, psoriasis, alopecia areata etc. When involving all the finger and toe nails bilaterally, it is referred to as ‘twenty nail dystrophies. We, hereby, report a case of trachyonychia in an 8-year-old boy, with concomitant lichen planus and alopecia areata. He was successfully treated with biweekly pulse systemic corticosteroid therapy for duration of 6 months. Significant response was noted at the end of 6 months in terms of hair re-growth; improvement of nail texture, thickness and subungual hyperkeratosis; and resolution of skin lesions.